Faktor-faktor yang mempengaruhi penerimaan retribusi daerah di Kota Jambi - Ica Romiyati; Yulmardi Yulmardi; Adi Bhakti (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2019)
This study aims to determine the development of the population, economic growth, regional spending, and regional retribution, to determine the effect of population, economic growth and regional spending on regional retribution in the city of Jambi from 2000-2016. The type of data used is secondary data obtained from the Central Statistics Agency (BPS). This research uses descriptive and quantitative analysis methods using multiple regression OLS methods. The results showed the population, economic growth, regional expenditure, and regional retribution increased from 2000-2016. Based on the results of multiple regression OLS methods show the population, economic growth, and regional spending have a significant effect on regional retribution in the city of Jambi in 2000-2016.